Silvopastoral systems in Portugal: Current status and future prospects - Castro, M (Agroforestry in Europe: Current Status and Future Prospects., 2008)
Portugal has a high diversity of agroforestry systems like other Mediterranean countries. This is the result of the Mediterranean climate, great variability of bioclimatic conditions, a long history of land use, and a marked variation in land tenure between north and south of the country. Four major silvopastoral systems are described: two classically Mediterranean – montado and Olive tree system, and two typically of the transitional environment between Mediterranean and Temperate conditions – Pyrenean oak and Chestnut systems. Some products of traditional agroforestry systems such as charcoal, organic manure, livestock production and others have become less valuable with the socio-economic transformation of the 1960s. These systems have been declining from approximately 1950 onwards. Currently, the focus on sustainable agriculture, with greater emphasis on nature and landscape conservation, has meant that environmental values now represent new opportunities for income generation from these systems. A better understanding of traditional agroforestry systems is needed for the formulation of a specific European policy that will preserve European landscapes. This paper looks at the future potential for silvopastoral systems in Portugal based on current status.
Keywords: chestnut systems; montado; olive tree system; Portugal; pyrenean oak system

Silvopastoral systems in Portugal: Current status and future prospects - Castro, M. (Agroforestry in Europe: Current Status and Future Prospects., 2008)
Portugal has a high diversity of agroforestry systems like other Mediterranean countries. This is the result of the Mediterranean climate, great variability of bioclimatic conditions, a long history of land use, and a marked variation in land tenure between north and south of the country. Four major silvopastoral systems are described: two classically Mediterranean – montado and Olive tree system, and two typically of the transitional environment between Mediterranean and Temperate conditions – Pyrenean oak and Chestnut systems. Some products of traditional agroforestry systems such as charcoal, organic manure, livestock production and others have become less valuable with the socio-economic transformation of the 1960s. These systems have been declining from approximately 1950 onwards. Currently, the focus on sustainable agriculture, with greater emphasis on nature and landscape conservation, has meant that environmental values now represent new opportunities for income generation from these systems. A better understanding of traditional agroforestry systems is needed for the formulation of a specific European policy that will preserve European landscapes. This paper looks at the future potential for silvopastoral systems in Portugal based on current status.
The following values have no corresponding Zotero field: periodical: Agroforestry in Europe: Current Status and Future Prospects.
Keywords: chestnut systems; montado; olive tree system; Portugal; pyrenean oak system